2006
DOI: 10.1007/s00296-006-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing and cochlear function by DPOAE and audiometric tests in patients with ankylosing spondilitis

Abstract: The aim of this study was to investigate cochlear functions in patients with ankylosing spondilitis (AS). Prospective, case control study. Twenty-eight AS patients (56 ears) and 25 healthy control subjects (50 ears) were included in the study. Pure-tone audiometry at 250, 500, 1,000, 2,000, 4,000, 6,000 Hz and immittance measures including tympanometry and acoustic reflex and DPOAEs (Distortion Product Otoacoustic Emission) testing were performed in the patients and controls. Pure-tone audiometry findings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Low-frequency hearing threshold shift caused by endolymphatic hydrops or the loss of a certain percentage of apical hair cells [14,15]. Our patients had no defined symptoms of endolymphatic hydrops.…”
Section: Discussionmentioning
confidence: 65%
“…Low-frequency hearing threshold shift caused by endolymphatic hydrops or the loss of a certain percentage of apical hair cells [14,15]. Our patients had no defined symptoms of endolymphatic hydrops.…”
Section: Discussionmentioning
confidence: 65%
“…Erbek et al [8] found that the rates of reproducibility in transient evoked otoacoustic emission testing (TEOAE) were significantly lower in patients with AS than those in controls. Daglı et al [7] determined the same result with distortion product otoacoustic emission testing (DPOAE). According to Daglı et al [7] , high frequencies are organized in the basal part of the cochlea; therefore, the damage is in the outer hairy cells of basal and intermediate parts of the cochlea in patients with AS.…”
Section: Discussionmentioning
confidence: 88%
“…Daglı et al [7] determined the same result with distortion product otoacoustic emission testing (DPOAE). According to Daglı et al [7] , high frequencies are organized in the basal part of the cochlea; therefore, the damage is in the outer hairy cells of basal and intermediate parts of the cochlea in patients with AS. Nevertheless, Kahveci et al [9] did not find any cochlear dysfunction in patients with AS with regard to the audiological and DPOAE results.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both early-onset congenital hypothyroidism and environmental iodine deficiency may lead to hearing loss in both humans and rats [27,28] . Psaltakos et al [29] investigated the changes in audiometric thresholds and TE-OAE results in patients who had undergone total thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%